A Combined Panel of Salivary Biomarkers in de novo Parkinson's Disease. Issue 3 (2nd January 2023) - De Bartolo, Maria Ilenia; Vivacqua, Giorgio; Belvisi, Daniele; Mancinelli, Romina; Fabbrini, Andrea; Manzo, Nicoletta; Costanzo, Matteo; Leodori, Giorgio; Conte, Antonella; Fabbrini, Giovanni; Morini, Sergio; Berardelli, Alfredo
Abstract : Objective: To investigate molecular biomarkers of a‐synuclein and tau aggregation, autophagy, and inflammation in the saliva of de novo Parkinson's disease (PD) patients in comparison to healthy subjects (HS), and to correlate molecular data with clinical features of PD patients, in order to establish whether abnormalities of these parameters are associated with specific clusters of de novo PD patients, and their potential diagnostic power in differentiating PD patients from HS. Methods: We measured total and oligomeric a‐synuclein, total‐tau and phosphorylated‐tau, microtubule‐associated protein light chain 3 beta (MAP‐LC3beta), and tumor necrosis factor alpha (TNFalpha) in the saliva of 80 de novo PD patients and 62 HS, using quantitative enzyme‐linked immunosorbent Assay analysis. Results: Oligomeric a‐synuclein, total‐tau, MAP‐LC3beta, and TNFalpha levels resulted significantly higher in patients with respect to HS, while no significant differences were detected for total a‐synuclein or phosphorylated‐tau. Phosphorylated‐tau directly correlated with MAP‐LC3beta, whereas it inversely correlated with TNFalpha in PD patients. An inverse correlation was detected between MAP‐LC3beta and non‐motor symptoms severity. Principal Component Analysis showed that molecular and clinical parameters were independent of each other in de novo PD patients. Receiver operating characteristic curve analysis reported an accurate diagnostic performance of oligomeric a‐synuclein and MAP‐LC3beta. The diagnostic accuracy of total a‐synuclein increased when it was combined with other salivary biomarkers targeting different molecular pathways. Interpretation: Our study proposes a novel biomarker panel using saliva, a non‐invasive biofluid, in de novo PD patients, with implications in understanding the molecular pathways involved in PD pathogenesis and the relevance of different molecular pathways in determining clinical PD subtypes. ANN NEUROL 2023;93:446–459